Tingkat Kepuasan Nasabah Pada Bank Syariah Mandiri Cabang Bogor - Priyo Wismantoro; Fika Dwiyanti (STIE Binaniaga, 2008)
Business banking is a service business based on principles of trust and t5he customer is a major asset. Under conditions of business competition among banks strict bank that has resulted in only a competitive advantage (compatative advantage as well as a competitive advantage) who can reach the highest position in the eyes of cusmers or the public. Competitive advantage can be obtained from the quality of customer servicr, so the focus on customers (customer focus), responsive to the development of customer desires and continuously innovate is an acitivity that can be done to anticipate the cimpetitive conditions. In this case, the bank should always evaluate the quality of service given to customers and is reflected in the level of customer satisfaction obtained. Rate the quality of service branch of bank syariah mandiri bogor whole is still under service, because it still was below expectations, this is evident also that the general level of service is still not meeting customer expectations, because the level of hope (expectation0 the customer is generally higher than the level of performance (perfromance) or perception(perception)customer. Empathy dimension of service quality dimensions are most critical or have any impact on the most powerful influence on the level of satisfaction. In this case, the willingness og bank syariah mandiri branch bogor provide individual attention in serving its clients is crucial. Empathy dimension attributes inclide individual attention, operational time , personal attention, giving interests, and understand the needs. These attributes is the main priority of service quality improvements are intensive and comprehensive. Customer service strategy to be implemented by the management of bank syariah mandiri in perspective five dimensioris of service quality(tangibles, realiability,responsiveness, assurance and empathy) looks not optimal. In an effort to provide the best service (service excellence) and focus to the customer(customer focus), then the customer satisfaction can be obatained with significantly improved and the improvement of quality of serivice aspects and impticalions of the strategy need to be consldered